Fiqh al-Awlawiyat is the basis for education on halal food and beverage - Abdurrahman, Usamah; Ardiani, Yana Elita; Sa'adah, Yaumi (Journal of Halal Science and Research, 2025)
This study aims to elaborate on the conception of halal and its education in the contemporary context and explain how fiqh al-awlawiyat can be applied as a basis for halal education in food and beverage products. After explaining halal as Islamic ethics and morality at different levels, it is explained how fiqh al-awlawiyat is highly urgent in its operation. In the final section, by parsing several fiqh al-awlawiyat rules, four recommendations are given, namely: (1) qualitative indicators of halal achievements need to be proclaimed as a foundation for quantitative indicators that have so far been applied, (2) halal educators need to be equipped not only with practical knowledge about the administrative aspects of halal certification, but also more sophisticated scientific tools such as fiqh al-awlawiyat, fiqh al-waqi', fiqh al-maqasid, and so on, (3) in the education process, educators need to pay attention to the gradual process by directing business partners to take care of their compliance with halal values respectively starting from reciprocal ethics, tolerant ethics, and altruistic ethics based on their abilities, and (4) the education process should not end when halal certification has been obtained but continued so that it can reach a higher level.   Keywords: Education, Fiqh al-Awlawiyat, Food and Beverages, Halal, Islamic Ethics.